Television and Contraceptive Use – Panel Evidence from Rural Indonesia - Jörg Peters; Christoph Strupat; Colin Vance (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
In recent years, rural electrification and access to television have spread rapidly throughout the developing world. The values and cultural norms embodied in television programming have potentially profound implications for infl uencing behavior, particularly as regards reproductive decisions. Using household panel data from the Indonesian Family Life Survey (IFLS), this paper explores the eff ect of television ownership on the use of modern contraceptives in rural Indonesia. Although results from a pooled regression suggest a statistically signifi cant and positive relationship between contraceptive use and television ownership, this fi nding is not robust to fixed effects estimates that control for time-invariant unobserved characteristics. By contrast, several other individual and community-level determinants, most notably the presence of midwives and health services, are statistically significant in the fixed effects model. We conclude that the growing corpus of cross-sectional evidence on a link between television and contraception should be interpreted cautiously. – – Dieses Papier untersucht mit Paneldaten des Indonesian Family Life Survey (IFLS), inwieweit die Nutzung von Fernsehgeräten das Fertilitäts- bzw. Verhüttungsverhalten von Frauen im ländlichen Indonesien beeinflusst. Die Ergebnisse der Untersuchung zeigen einen positiven und signifikanten Zusammenhang zwischen der Nutzung von Fernsehgeräten und der Verwendung von Verhüttungsmitteln, wenn zeitinvariante und unbeobachtete Heterogenität in den Schätzungen nicht berücksichtigt wird. Die Eliminierung dieser Faktoren mittels einer Fixed-Effects- Transformation zeigt jedoch, dass die Nutzung von Fernsehgeräten keinen signifikanten Einfluss auf den Gebrauch von Verhüttungsmitteln hat. Im Gegensatz dazu erhöhen zahlreiche regionale Faktoren, wie Krankenstationen oder Hebammen im Dorf, die Nutzung von Verhüttungsmitteln. Der Einfluss des Fernsehens ist somit bei Nicht- Berücksichtigung der zeitinvarianten und unbeobachteten Heterogenität überschätzt.
Keywords: J13; O12; O33; 330; contraceptive use; television; fertility; technology adoption; rural development